Dekonstruksi Gelar Haji: Analisis Sosiologis tentang Stratifikasi Sosial dan Dampaknya di Masyarakat - Armeta, Armeta; Daffa Nasywa Afriani; Indra Abdul Majid; Renitadewi Kusumah Wardani; Siti Komariah; Pandu Hyangsewu (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2024)
In terms of religion, the Hajj pilgrimage is a sense of our faith and religion to Allah SWT, through a long historical story of the use of the term